(untitled) (Cambridge UK, 2001)
Injury Control: Research and Program Evaluation addresses the growing need for a single comprehensive source of data on all research designs available for injury control and research. This accessible guidebook includes information on research tools such as injury severity scales, conducting program evaluations and trauma audits, systematic reviews, and ecologic studies. Epidemiologists and health service investigators, as well as trauma surgeons and emergency medicine physicians who provide the post-acute care of trauma patients, will find this the only current information source focused on injury control research and evaluation.
Keywords: Accidents,Tai nạn,Wounds and injuries,Thương tích; Prevention,Research,Phòng tránh,Nghiên cứu,Prevention,Research,Phòng tránh,Nghiên cứu